TAX CONSIDERATIONS IN INTRACOMPANY PRICING. - Stone, Williard E. (The Accounting Review, 1960)
Abstract When products are transferred among the corporate units of a family of corporations, a "sales" price must be established to properly ac- count for the transfer. The intracompany transfer price may or may not contain an element of profit to the selling unit. The decision to use one basic type of system, i.e. containing an element of profit or not, has, therefore, a definite effect upon the amount of net income and consequently upon the amount of tax paid by a family of corporations. The fact that by intracompany pricing a corporation may transfer net income from one unit to another assumes importance because of the structure of the United States corporate net profits tax. The application of this section is limited to transfers of property from a corporation to a newly created or reactivated corporation under common control. The purpose of this section of the code is to prevent the arbitrary shifting of net income among taxable units of a family of corporations in order to prevent the evasion of tax liability. The requirement that transfer price be the equivalent of fair market value could be difficult. If strictly applied by the Director of Internal Revenue and if upheld by the courts, this requirement could, for tax Purposes, restrict intracompany pricing to one method-market.